The very hungry caterpillar - Carle, Eric. (Collins Publishers, 1979)
Follows the progress of a hungry little caterpillar as he eats his way through a varied and very large quantity of food until, full at last, he forms a cocoon around himself and goes to sleep. Die-cut pages illustrate what the caterpillar ate on successive days.